Quadruple Helix Concept in Improving Community Living Standards Through the Development of Micro, Small and Medium Enterprises (MSMEs) in Rempek Darussalam Village - Rulah, Kama; Nusamuda Pratama, Inka; Amil, Amil (Lembaga Penelitian dan Pendidikan Mandala, 2023)
The Quadruple Helix concept is a collaboration of four sectors, namely government, private sector, academics and civil society. Involvement and performance carried out by various stakeholders in improving living standards through the development of micro, small and medium enterprises. The research method used in this research is qualitative. The results of this research show that the development of micro, small and medium enterprises in an effort to improve people's living standards has been pursued by various policy stakeholders starting from the government, private sector/business world, academics and the community, although there are still many shortcomings in the beginning. from the government and the private sector/business world which is still lacking. stiff and still less active, especially in providing training and providing capital, as well as from the academic side which is still less effective in training, mentoring, digital marketing socialization.